Strategi Kepala Madrasah dalam Meningkatkan Profesionalisme Guru pada Mata Pelajaran Akidah Akhlaq - Putri Dwi Sari; Siti Maratus Solekha; Ibnu Sodik (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aimed to analyze the professionalism of Aqidah Akhlak teachers, describe the strategies employed by the madrasah principal to improve teacher professionalism, and identify the supporting and inhibiting factors at MA Al Fakhriyah Baturaja. The study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that the professionalism of Aqidah Akhlak teachers was generally in a good category, as reflected in their ability to plan, implement, and evaluate learning while continuously improving their professional competence. The principal's strategies included academic supervision, professional coaching, motivation, facilitation of training programs and subject teacher forums (MGMP), and the development of a collaborative work culture. Supporting factors consisted of the principal's commitment, teachers' motivation, effective communication, and a conducive organizational culture, whereas the inhibiting factors included limited opportunities for professional development, inadequate facilities and infrastructure, and varying levels of teachers' readiness to improve their competencies. The study concludes that effective madrasah leadership plays a significant role in strengthening teacher professionalism and improving the quality of learning in Islamic schools.